Contribution to the knowledge of the Rubiaceae of the Lesser Antilles: Martiniques case. - CLAUDE, Jean-Philippe; baillard, Kevine; Marius, Severine Ely; Yanis, Jean Francois (JOURNAL OF ADVANCES IN BIOLOGY, 2017)
The Rubiaceae represent one of the worlds five largest families of flowering plants. This family is diversified in terms of number of species, genera, physiognomic types or chemical spectra. Within their flora the Lesser Antilles (part of one of the worlds biodiversity hot spots) accommodate part of this diversity, originating from tropical America. In order to enrich our knowledge of the Rubiaceae of the West Indies, we carried out a study in forest ecology in Martinique. The aim was to determine the chorology of the Rubiaceae species and their functions as well as to identify their various ethnobotanical uses. The place of the Rubiaceae in Martiniques plant dynamics, the factorial conditions that favour their settlement and distribution have thus been defined using data from the world scientific literature, regional floras and field surveys. It is clear that this family occupies a wide range of habitats. The Rubiaceae are present in all bioclimates (dry to wet), in various plant formations at various stages of evolution. We recorded 89 Rubiaceae species divided in 41 genera. All forms of life are represented ranging from trees to grasses, through lianas and epiphytes. The Rubiaceae are an essential component of our regions flora; nevertheless their diversity is weakened by a strong degree of anthropisation characterised by environmental damage.